Design of an open large wind tunnel for wind turbine testing - Chan, Aloysius Wei Yong. (2013)
Wind tunnels are used in aerodynamic studies on the effect of air moving across the test specimen mounted in the middle of the tunnel. They are structurally constructed by large tubes filled with air travelling along the passage path of the tunnel. In this Final Year Project, a large open test section wind tunnel is designed and a prototype is manufactured.